The Influence of Student’s Understanding of Information and Technology Law on Shaping Character - Syaifudin, Ahmad; Krestian Heriawanto, Benny; Al-Abrori, M. As'Ad; Humairoh, Anisatul (JURNAL USM LAW REVIEW, 2024)
This study aims to analyze the influence of information and communication technology and the impact of technology use in higher education institutions, with the Islamic University of Malang as the scope of respondents. Technology is a crucial issue to discuss today because all human activities require adequate technology, one of which is the field of education. The urgency of this research is that technology is one of the supports for the success of education at the Islamic University of Malang. However, on the other hand, technology can sometimes be detrimental to students who need to be aware of the law. These losses can potentially lead to criminal acts. The novelty of this research is that it specifically examines the effect of students’ understanding of legal provisions related to information and technology in Indonesia and the importance of knowing the legal consequences if technology is not used appropriately by students so that this research becomes a new contribution. This writing uses empirical juridical research, primary and secondary data, and a questionnaire approach. The results showed that using technology and information provides a way to improve skills, economic welfare, economic science, and especially education. It is necessary to increase the legal understanding of information technology among students by providing training and education.